(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2018)
Therapists have access to reports of events occurring outside the session rather than the events themselves, making the accuracy of reports fundamental to psychotherapy. This paper aims to discuss how the regularities described in reports of basic research in verbal correspondence can help analytic-behavioral therapists understand variables that interfere the accuracy of verbal reports. This theoretical approach will present the fundamental concepts and the main data of basic research in verbal correspondence, which will be applied in the understanding of clinical examples. Still based on the examples, it will be discussed how some practices of therapists can affect the verbal correspondence of their clients. It is concluded that the way in which questions requesting the reports, the consequences presented by the therapist to the client’s behavior and the manner which the rules are manipulated, are all variables that affect the verbal correspondence in the clinic.